INTEGRATION OF MODERN SOIL SCIENCE, INTEGRATED FARMING, AND NIAS LOCAL WISDOM FOR AGRICULTURAL PRODUCTIVITY IMPROVEMENT - Darmawan Harefa (Jurnal Sapta Agrica, 2025)
This study explores the integration of modern soil science, integrated farming systems (IFS), and Nias local wisdom to improve agricultural productivity in Desa Bawonifaoso, Kecamatan Teluk Dalam, Kabupaten Nias Selatan. The research aims to examine how combining scientific soil management practices with diversified farming techniques and traditional knowledge can enhance crop yields, environmental sustainability, and community resilience. Using a qualitative literature review approach, data were collected from scientific journals, books, conference proceedings, and credible online sources that discuss soil fertility, integrated farming, and the application of local wisdom in agriculture. The findings indicate that modern soil science interventions such as soil testing, rational nutrient management, and organic amendments can optimize soil fertility and crop growth. When applied alongside integrated farming practices and local wisdom traditions, such as communal land management, crop rotation aligned with cultural calendars, and organic residue utilization, farmers achieve higher yields, reduced dependency on chemical inputs, and improved environmental sustainability. Furthermore, integrating these approaches strengthens community engagement and knowledge transfer, ensuring sustainable adoption. The study concludes that the tripartite integration of modern soil science, IFS, and local wisdom offers a holistic, culturally appropriate, and environmentally sustainable model for agricultural development. It is recommended that agricultural extension programs and policymakers support this integrated approach to enhance productivity, resilience, and food security in rural Indonesian communities.